2004
DOI: 10.1002/eqe.366
|View full text |Cite
|
Sign up to set email alerts
|

Correlating measured and simulated dynamic responses of a tall building to long‐distance earthquakes

Abstract: SUMMARYFor almost a decade, a 66-storey, 280 m tall building in Singapore has been instrumented to monitor its dynamic responses to wind and seismic excitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In 2001, based on the finite element (FE) code of LS-DYNA, Lu et al [10] developed an FE model to simulate the collapse process of the World Trade Center in New York, which had been impacted by aircraft, and explained the main reasons for the progressive collapse. In 2004, Pan and Brownjohn [11] presented a numerical study on the dynamic responses of the tallest building in Singapore and compared the FE results with 21 field measurements of the structural response to far-field ground motions. The predicted roof displacement of the structure agreed well with the field observations.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, based on the finite element (FE) code of LS-DYNA, Lu et al [10] developed an FE model to simulate the collapse process of the World Trade Center in New York, which had been impacted by aircraft, and explained the main reasons for the progressive collapse. In 2004, Pan and Brownjohn [11] presented a numerical study on the dynamic responses of the tallest building in Singapore and compared the FE results with 21 field measurements of the structural response to far-field ground motions. The predicted roof displacement of the structure agreed well with the field observations.…”
Section: Introductionmentioning
confidence: 99%
“…A reducedorder continuum model was proposed by Chajes et al [12] to conduct dynamic analysis of a 47-storey steel-framed building and correlate the numerical results with those from measured responses during an earthquake. Pan et al [13] and Brownjohn et al [14] presented numerical studies on dynamic responses of the tallest building in Singapore with correlation with their field measurements. Qi et al [15] employed the finite element method to study the seismic performance of a tall building and their results illustrated that the building is likely to perform satisfactorily under severe seismic events.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, several studies reported significant effects at greater distances. For example, a 17‐story building in Singapore founded on soft soil at an epicentral distance of 750 km was self‐evacuated during the 1994 M w 7.0 Liwa earthquake in Sumatra . More recently, Çelebi et al studied the response of tall buildings located at 388 and 770 km from the epicenter during the 2011 M w 9.0 Tohoku earthquake and its aftershocks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 17-story building in Singapore founded on soft soil at an epicentral distance of 750 km was self-evacuated during the 1994 M w 7.0 Liwa earthquake in Sumatra. 3,4 More recently, Çelebi et al studied the response of tall buildings located at 388 and 770 km from the epicenter during the 2011 M w 9.0 Tohoku earthquake and its aftershocks. These studies emphasize the need to consider risk from distant sources in built environments and show that the prolonged response of buildings due to distant earthquakes is a consequence of the effects of traveling long-period motions and a combination of site resonance and low damping of the structures.…”
Section: Introductionmentioning
confidence: 99%